Interpretasi Perspektif Kesehatan atas Fatwa Syekh Muhammad Arsyad Al Banjari dalam Kitab Sabilal Muhtadin tentang Kehalalan Memakan Haliling (Bekicot Sawah) dan Keharaman Memakan Anak Wanyi (Anak Lebah) - Farhan Fauzi Hasbi; Fariq Nur Ulya; Abdurrahman Abdurrahman (Asosiasi Riset Ilmu Pendidikan Agama dan Filsafat Indonesia, 2024)
This study explores the fatwa of Sheikh Muhammad Arsyad Al Banjari in the book Sabilal Muhtadin regarding the permissibility of eating haliling (field snails) and the prohibition of eating anak wanyi (bee larvae) with a focus on the health perspective. Sheikh Muhammad Arsyad Al Banjari stated that snails are halal food, while bee larvae are considered haram. This study uses a literature study method to analyze the legal basis and health implications of both types of food. The results of the study indicate that snails can be safely consumed if processed properly, because snails are rich in protein and nutrients, but require special attention in processing to avoid the risk of infection from parasites or bacteria. Conversely, consuming bee larvae can pose health risks such as allergic reactions and dangerous toxins, and can have a negative impact on the bee population and ecosystem. The conclusion of this study emphasizes the importance of understanding fatwas from a health and ethical perspective, as well as the need for education regarding food processing practices that are in accordance with sharia principles and modern health standards.